Determination of Building Assets and Equipment Requirements Based on Sustainable Warehouse Cencepts for PT Kansai Prakarsa Coatings - Purnama, Putri Dewi; Azizah, Halla Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Warehouses play a crucial role in supporting the performance of companies in the logistics sector. PT Kansai Prakarsa Coatings (KPC) is a subsidiary of Kansai Paint Co., Ltd., a company in the paint industry sector. The distribution office and warehouse of the Bandung branch of PT Kansai Prakarsa Coatings (KPC) are located at Amir Machmud Street, Number 361, Cigugur Tengah Village, Cimahi Tengah, District, Cimahi City. The total area of the warehouse building is 408 m², with a total capacity of 80 tons. Several key issues have been identified, including poor ventilation and lighting in the closed warehouse, non-compliant loading conditions that do not meet applicable standards, and cases of overloading despite potential development. Since paint is a flammable product, it is necessary to have safe storage facilities. Additionally, paint has a strong odor and contains chemicals, making it essential to store it in a room with good ventilation and air circulation. Based on these main issues, it is important to conduct research to determine the need for building assets and warehouse equipment for PT Kansai Prakarsa Coatings, following the principles of a sustainable warehouse. The ; study is guided by SNI 7331:2007 and incorporates the concept of a sustainable warehouse. Descriptive methods with both qualitative and quantitative approaches were used in this study. Data collection techniques included interviews, observations, and documentation studies. The results of the study indicate that the total additional area required for the warehouse building is 372 m². This calculation is based on the estimated load of products stored both inside and outside the warehouse. Regarding warehouse equipment, based on the concept of a sustainable warehouse, PT Kansai's warehouse needs to procure ventilation systems, occupational health and safety equipment, lighting systems, as well as shelving and material handling equipment.